OP0004 Visceral Fat Measured by Dual-Energy X-Ray Absorptiometry is Associated with Increased Risk of Non-Spine Fractures in Nonobese Elderly Women: A Population-Based Prospective Cohort Analysis from The São Paulo Ageing & Health (Spah) Study. (9th June 2015) - Machado, L.G.; Domiciano, D.; Figueiredo, C.; Lopes, J.; Caparbo, V.; Takayama, L.; Oliveira, R.; Pereira, R.M.R.
Abstract : Background: The protective role of obesity on bone health has currently been questioned, since it has been demonstrated that visceral fat have a deleterious effect on bone. However, there are no studies evaluating the association between visceral fat measured by DXA with fracture risk. Objectives: The aim of this study was to investigate the association of visceral fat with incident non-spine fractures in community-dwelling elderly women. Methods: This is a longitudinal prospective population-based cohort study evaluating 433 community-dwelling women aged 65 years or older. Specific questionnaire (clinical and anthropometric data), including personal history of fragility fracture in non-spine osteoporotic sites (hip, humerus, wrist, rib) was performed at baseline and after an average of 4.3 years. All incident fractures during the study period were confirmed by affected site radiography. Bone mineral density (BMD) and laboratory tests were also performed at baseline. Visceral fat was measured by a new software of dual-energy X-ray absorptiometry (DXA) in the android region of a total body DXA scan. Logistic regression models were used to estimate the relationship between visceral fat and non-spine fractures. Results: The mean age was 72.8±4.7 years and 28 incident non-spine osteoporotic fractures were identified after a mean follow-up time of 4.3±0.8 years. According the Lipschitz classification for nutritional status in elderly, 61.4% of women were considered obese/overweigth (BMI >27 kg/m 2 ) and 38.6% were nonobese (7.4% underweight- BMI <22 kg/m 2 and 31.2% normal weight- BMI ≥22 and ≤27 kg/m 2 ). After adjusting for age, previous fracture and BMD (parameters with significance at univariate analysis), visceral fat area had a significant association with incident non-spine fractures in nonobese (BMI ≤27 kg/m 2 ) elderly women (p=0.009). Conclusions: Higher visceral fat was associated with the risk for non-spine fractures in nonobese elderly women. This study supports a potential negative effect of visceral adiposity on bone health. References: Gower BA, Casazza K. Divergent effects of obesity on bone health. J Clin Densitom. 2013;16(4):450-454. Cohen A, Dempster DW, Recker RR, et al. Abdominal fat is associated with lower bone formation and inferior bone quality in healthy premenopausal women: a transiliac bone biopsy study. J Clin Endocrinol Metab. 2013;98(6):2562-2572. Sheu Y, Marshall LM, Holton KF, et al. Abdominal body composition measured by quantitative computed tomography and risk of non-spine fractures: the Osteoporotic Fractures in Men (MrOS) Study. Osteoporos Int. 2013;24(8):2231-2241. Lipschitz DA. Screening for nutritional status in the elderly. Prim Care. 1994; 21(1):55-67. Disclosure of Interest: None declared